The Effectiveness Of Electronic Traffic Control Implementation In Reduce Motor Vehicle Accidents - Priyo Utomo; Lathifah Hanim (Universitas Islam Sultan Agung, 2021)
The rapid growth of the number of motorized vehicles that is not matched by the legal culture of the people who use motorized vehicles often results in an increase in the number of accidents. Electronic based traffic control. However, the lack of facilities and infrastructure for the implementation of electronic traffic control has resulted in the ineffectiveness of electronic traffic control, this also happened in the Grobogan area. This paper aims to further analyze the effectiveness of the implementation of electronic traffic control, especially in the Grobogan area. The method in this writing is qualitative descriptive. Based on the analysis carried out, it can be seen that the implementation of Electronic Traffic supervision in the Grobogan area has not been effective this is due to inadequate facilities and infrastructure. Then the factor of community obedience to the traffic rules that apply in Gobogan.